136k views
1 vote
11. Find the product of (3x+5) with (2x - 3) in simplest form.

User Osnoz
by
5.2k points

1 Answer

5 votes

Answer:

(3x + 5)(2x - 3) = 6x² + x - 15

Explanation:

To find the product of two binomials, we could use the FOIL method.

First

Outer (Outside)

Inner (Inside)

Last

(3x + 5)(2x - 3) = (3x)(2x) + (3x)(-3) + (5)(2x) + (5)(-3) = 6x² - 9x + 10x - 15 = 6x² + x - 15

So the product of the two binomials would be 6x² + x - 15.

I hope you find my answer and explanation to be helpful. Happy studying.

User Ian Sudbery
by
5.5k points